Disregulasi IL-17, CD4 neutrofil, IL-10, PGE-2, iNOS, dan MMP-9 di jaringan kulit terhadap kerusakan saraf dermal pada pasien erythema nodusum leprosum - I Gusti Nyoman Darmaputra; Cita Rosita Sigit Prakoeswa; Anang Endaryanto; IGAA Elis Indira; Nyoman Suryawati; Evy Ervianti; Linda Astari; Bagus Bagus (DiscoverSys Inc., 2019)
Introduction: The mechanism of nerve damage in ENL patients is important to be revealed because the problem of nerve damage is not getting enough attention in handling ENL patients. Some pro-inflammatory mediators that have been studied are risk factors for nerve damage in ENL.Aim: This study aim in knowing the mechanism of nerve damage in the relation with its risk factors, which are CD64 neutrophil, IL-17, MMP-9, and iNOS with PGE-2 and IL-10 protective factor and IL-10 in ENL patients.Method: This is an analytic cross-sectional design study with tissue samples from 30 leprosy patients with ENL in Dr. Soetomo General Hospital Surabaya. Samples from biopsy examined using IHC method to evaluate S-100, IL-10, IL-17, PGE-2, iNOS, MMP-9, and CD64 neutrophil expressions. The result calculated within 20 view field with 1000 times magnification.Result: CD64 neutrophil (p=0.022, r=-0.417), IL-17 (p=0.001, r=-0.560), iNOS (p=0.005, r=-0.502) and MMP-9 (p=0.025, r=-0.409) has significant correlation with S-100. There is no significant correlation between IL-10 (p=0.061) and PGE-2 (p=0.407) with S-100.Conclusion: Expressions of IL-17, CD64 neutrophil, MMP-9, and iNOS in tissue correlate with nerve damage in ENL patients.